The Role of Educational Institutions in Confronting Extremism, Violence, and Terrorism (School and University as a Model) - Abbas, Asst.L. Noor Mohammed Khudair Abbas (Sulaimani Journal for Humanities, 2026)
Educational institutions play a vital and distinguished role in confronting violence, extremism and terrorism by promoting positive values and providing an appropriate environment for individuals as violence has become prevalent in our society. Forms of confrontation have multiplied by teaching the emerging generation ethics and how to deal with members of society and working to refine and refine the individual's personality and help him integrate into society and remove the wrong ideas and beliefs that controlled his thoughts. The role of the school and university emerged in how to confront these extremist ideologies, as the research reached a set of results, the most important of which is the extent of the effectiveness of the role played by (school and university) alike, represented by the role of education first before (education), which is based on guiding and preparing the individual and qualifying him socially, psychologically and educationally The school is one of the means of social upbringing that works to raise the individual psychologically, socially and religiously to face life, i.e. transforming him from a biological being into a social being by instilling social values and customs and instilling the principles of tolerance, peace, love for others and rejection of violence and terrorism. Among the most prominent roles played by educational institutions, the research also clarified the role of awareness and education that it practices by educating students about the dangers of extremism and terrorism on the individual and society together, as it works hard to spread love, peace and cooperation through curricula and intensive lectures and enhance self-confidence and analyze ideas and confront negative ideas and reject them and not accept them. These institutions also clarified an important role for religion and the principles it carries that call for mercy, tolerance, peace and love and reject violence and extremism and correct the wrong concepts and ideas that extremists exploit in order to justify their actions, exploiting religion as a cover for them. These educational institutions are therefore the main pillar for building a healthy society free of dissolution, extremism and terrorism. The research reached several recommendations, the most important of which are: 1. Activating the role of educational institutions in confronting violence Terrorism through posters and ongoing discussion groups. 2. Providing psychological and social support to students who are vulnerable to being influenced by negative extremist ideas. 3. Enhancing the role of the family in monitoring and guiding the behavior of individuals because it is considered the first incubator for the individual and working to correct their behavior because it is a link between the individual and the school.
Keywords: Role; educational institutions; extremism; terrorism; violence